Education: 5. Application of Interactive Methods to Music and Literature Lessons in Primary Classes - Gînju Tatiana (Sciendo, 2018)
The author takes over and presents in the context of the action of integrating the literary-artistic education methodologies - the musical education methodologies the epistems that explain the interactive nature of these. This original way of approaching literature and arts methodologies has been applied experimentally in primary education, language courses and romanian literature and music education, thus providing teaching staff with integrated teaching and learning materials of literature and music.